A dual-switch cubic SEPIC converter with extra high voltage gain - Christophe Raoul Fotso Mbobda; Alain Moise Dikandé (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
To provide a high votage conversion ratio, conventional non-isolated DC-DC boost topologies, which have reduced voltage boost capability, have to operate with extremely high duty cycle ratio, higher than 0.9. This paper proposes a DC-DC converter which is mainly based on the narrow range of duty cycle ratio to achieve extra high voltage conversion gain at relatively reduced voltage stress on semiconductors. In addition, it does include any magnetic coupling structure. The structure of the proposed converter combines the new hybrid SEPIC converter and voltage multiplier cells. From the steady-state analysis, this converter has wide conversion ratio and cubic dependence with respect to the duty ratio and then, can increase the output voltage several times more than the conventional and quadratic converters at the same duty cycle ratio. However, the proposed dual-switch cubic SEPIC converter must withstand higher voltage stress on output switches. To overcome this drawback, an extension of the proposed converter is also introduced and discussed. The superiority of the proposed converter is mainly based on its cubic dependence on the duty cycle ratio that allows it to achieve extra high voltage gain at reduced voltage stress on semiconductors. Simulation results are shown and they corroborate the feasibility, practicality and validity of the concepts of the proposed converter.